Ethnopedagogy: Traditional games in senior high school physics enrichment module - Yuberti, Yuberti; Komikesari, Happy; Asyhari, Ardian; Octana, Iis Nanda (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
This research aims to determine expert opinions on the feasibility of high school physics enrichment modules with 21st-century skills based on ethnopedagogy and determine the product's attractiveness. This research employed R and D research in conjunction with ADDIE development models. The research subjects were senior high school students from MAN 1 Bandar Lampung, SMA Negeri 12 Bandar Lampung, and SMA Negeri 5 Bandar Lampung. The data collection techniques were questionnaires for expert validation: material expert, media expert, and cultural expert. Then the researchers also distributed student questionnaires. The findings of this study are as follows: 1) the final product met the excellent criteria, 2) the product's attractiveness met the excellent criteria, and 3) the teachers’ responses indicated that the product belonged to the excellent criteria. As a physics learning product, the high school physics enrichment modules with 21st-century skills based on ethnopedagogy were appropriate and attractive to use. It is suggested that further researchers develop learning material other than local Lampung culture and traditional Lampung games so that the physics concepts will differ.